Physiological Signatures of Changes in Honeybee's Central Complex During Wing Flapping. Issue 5 (12th October 2022) - Ding, Haojia; Yan, Shaoze
Abstract: Many kinds of locomotion abilities of insects-including flight control, spatial orientation memory, position memory, angle information integration, and polarized light guidance are considered to be related to the central complex. However, evidence was still not sufficient to support those conclusions from the aspect of neural basis. For the locomotion form of wing flapping, little is known about the patterns of changes in brain activity of the central complex during movement. Here, we analyze the changes in honeybees' neuronal population firing activity of central complex and optic lobes with the perspectives of energy and nonlinear changes. Although the specific function of the central complex remains unknown, evidence suggests that its neural activities change remarkably during wing flapping and its delta rhythm is dominative. Together, our data reveal that the firing activity of some of the neuronal populations of the optic lobe shows reduction in complexity during wing flapping. Elucidating the brain activity changes during a flapping period of insects promotes our understanding of the neuro-mechanisms of insect locomotor control, thus can inspire the fine control of insect cyborgs.